Recurrent Miscarriage and Micro-RNA Among North Indian Women - Parveen, Farah (Reprod Sci, 2014)
Micro-RNAs (miRNAs) regulate diverse cellular processes such as cell differentiation, proliferation and apoptosis. Mutation in miRNAs results in various pathological conditions such as inflammation, viral infections, neurodegeneration, autoimmunity, and so on. We have evaluated the association of miR-146aC > G (rs2910164), miR-149T > C (rs2292832), miR-196a2T > C (rs11614913), and miR-499A > G (rs3746444) among patients with recurrent miscarriage (RM) and controls from North India. All the 200 patients with RM reported to experience at least 3 unexplained miscarriages before 20th week of gestation. Three hundred fertile women with no history of RMs were taken as controls. Both patients and controls were genotyped by the polymerase chain reaction amplification followed by restriction fragment length polymorphism. Variant alleles and genotypes of miR-499 A > G (Single Nucleotide Polymorphism Database [dbSNP] ID rs3746444) were found to be significant risks associated with patients having RM (odds ratio [OR] = 1.98; 95% confidence interval [CI] = 1.40-2.81; P value = .0001) and controls (OR = 3.64; 95% CI = 1.33-9.94; P value = .0109). A significant susceptible effect was found at allelic level in miR-196aT > C (dbSNP ID rs11614913) and miR-499 A > G (dbSNP ID rs3746444).